2020
DOI: 10.21203/rs.3.rs-80139/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Validation of the Functions and Prognostic Values of Synapse Associated Proteins in Lower-Grade Glioma

Abstract: Background: Synapse and synapse associated proteins (SAPs) play critical roles in various neurodegeneration diseases and brain tumors. However, in lower-grade gliomas (LGG), SAPs have not been explored systematically. Herein, we are going to explore SAPs expression profile and its clinicopathological significance in LGG which can offer new insights to glioma therapy. Method: In this study, we used five sources including, Venkatesh, Shen, Colón, Jüttner R, Gene Ontology (GO) project to integrate a list of SAPs … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Studies by Lin et al suggest that differentially expressed synapses and synapse-associated proteins (SAPs) may be involved in the formation of glutamate synapses and LGG synapses. Furthermore, they found that SAPs might be related to the pathogenesis of seizures in glioma patients [21]. KEGG pathway analysis indicated the functions of DEGs were mainly concentrated in the Notch, Hippo, and cAMP signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Lin et al suggest that differentially expressed synapses and synapse-associated proteins (SAPs) may be involved in the formation of glutamate synapses and LGG synapses. Furthermore, they found that SAPs might be related to the pathogenesis of seizures in glioma patients [21]. KEGG pathway analysis indicated the functions of DEGs were mainly concentrated in the Notch, Hippo, and cAMP signaling pathways.…”
Section: Discussionmentioning
confidence: 99%